(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
Knowledge is crucial for companies, providing competitive advantages. However, the management of knowledge faces challenges, especially in public companies. Since 1995, the management culture of knowledge in Brazilian public companies has been in transformation. The Alagoas State Research Support Foundation created a training and qualification support program for servers, aiming to improve their professional skills and performance of functions, as well as increase personal satisfaction. This program preceded the new functions, being pioneering and influencing the current Plan of Positions, Careers and Salários of the Foundation.